ЩОДО ВИЗНАЧЕННЯ СУТНОСТІ АДМІНІСТРАТИВНОЇ ДІЯЛЬНОСТІ ПАТРУЛЬНОЇ ПОЛІЦІЇ - Циркулєнко, С. С. (Вісник Пенітенціарної асоціації України, 2025)
The article provides a comprehensive scientific and theoretical analysis of the concept and types of administrative activity of the Patrol Police as a key component in the implementation of the state’s law-enforcement function. It is determined that the administrative activity of the Patrol Police has a systemic nature and encompasses both external (law-enforcement, security, jurisdictional) and internal organizational (managerial, personnel-related, regulatory) dimensions, which determines its complexity and multidimensional character. Based on the generalization of doctrinal approaches, the author formulates a definition of the administrative activity of the Patrol Police as a subordinate executive-administrative activity aimed at protecting human rights and freedoms, ensuring public safety and order, preventing and stopping offences, ensuring road-traffic safety, and organizing the proper functioning of police units. A classification of the main types of external administrative activity of the Patrol Police is provided, including the protection of human rights and freedoms, ensuring public safety and order, implementation of administrative coercive measures, administrative-jurisdictional procedures, and providing assistance to citizens. Particular attention is paid to internal organizational activity as an essential prerequisite for the effectiveness of external law-enforcement measures. The role of normative legal regulation is emphasized, as it defines the limits of police powers and establishes standards of legality, proportionality, and respect for human rights in the course of administrative actions. The results of the study make it possible to form a coherent understanding of the structural and functional content of the administrative activity of the Patrol Police, which is significant for improving law-enforcement practice and advancing the theory of modern administrative law.